Family businesses restrict accrual and real earnings management: Case study in Saudi Arabia - Adeeb Abdulwahab Alhebri; Shaker Dahan Al-Duais (Cogent Business & Management, 2020)
This paper investigates accrual earnings management (AEM) and real earnings management (REM) in family businesses (FB) in Saudi Arabia. Current literature indicates that minority rights are confiscated by the controlling shareholders in a business environment weak to protect investors. Based on this argument, considering the various implications of AEM and REM on family businesses, the results show evidence that family businesses in Saudi Arabia engaged in both types of earnings management during the period 2014-2018, with a positive and significant effect on both AEM and REM. This evidence supports the entrenchment hypothesis that FB have lower earnings quality due to manipulation in accruals and real activities. The results therefore indicate that earnings announced in Saudi family businesses' financial statements are less reliable. These findings, that family-controlled firms are able to manipulate earnings, should be considered by regulators and policy makers.
Keywords: 650; family businesses; real earnings management; accrual earnings management